Comparative Analysis of Risk and Return on Bitcoin, Stocks, and Mutual Funds in Investment Decisions - Sia Lily Bramaputri; Sri Handayani; Dheny Biantara; Ratna Dina (Jurnal Multidisiplin Sahombu, 2026)
This study aims to analyze and compare the risk and return characteristics of three investment instruments representing different asset classes, namely Bitcoin as a cryptocurrency asset, the S&P 500 index as a representation of the conventional stock market, and Invesco QQQ as an exchange-traded fund (ETF)-based mutual fund. The study uses a descriptive quantitative approach by utilizing secondary data in the form of monthly closing prices during the period from January 2020 to December 2024. The analysis is conducted through the calculation of average monthly returns, risk measured using standard deviation, and the coefficient of variation to assess risk efficiency relative to returns. The research results show that Bitcoin has the highest average monthly return of 6.21% along with the highest level of volatility, reflecting the characteristics of a high-risk investment. The S&P 500 index shows the lowest average return of 1.08% with the highest coefficient of variation, indicating relatively low risk efficiency. Meanwhile, the Invesco QQQ ETF shows a balance between risk and return with a better level of efficiency compared to the S&P 500. These findings confirm that the relationship between risk and return differs significantly across investment instruments, so investment decisions need to be adjusted according to the investor's risk profile and financial goals.